ENHANCEMENT OF GLIBENCLAMIDE DISSOLUTION RATE BY SOLID DISPERSION METHOD USING HPMC AND PVP - BUDIMAN, ARIF; SOPYAN, IYAN; RIYANDI, DENIA SEPTY (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study was to investigate the effects of changing in the proportions of the solid dispersion formula on the dissolution rate of glibenclamide. Methods: Solid dispersions were prepared by solvent evaporation method by using methanol as solvent, hydroxypropyl methylcellulose (HPMC) and polyvinyl pyrrolidone (PVP) as polymers. The prepared product was evaluated by the saturated solubility test and the dissolution rate test. The prepared product was characterized by Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), and powder X-ray diffraction (PXRD) and Scanning Electron Microscopy (SEM). Results: The result showed solid dispersion with a ratio of glibenclamide: PVP: HPMC (1: 3: 6) has the highest increase in solubility (20 fold) compared to pure glibenclamide. This formula also showed an improvement in dissolution rate from 19.9±1.19% (pure glibenclamide) to 99±1.60% in 60 min. Characterization of FT-IR showed that no chemical reaction occurred in solid dispersion of glibenclamide. The results of X-ray diffraction analysis showed an amorphous form in all solid dispersion formulas. The results of DSC analysis showed that endothermic peak melting point of solid dispersion occurred, and the morphology of solid dispersion was more irregular than pure glibenclamide based on SEM characterization Conclusion: The solid dispersion of glibenclamide using PVP: HPMC as carriers can increase the solubility and dissolution rate compared to pure glibenclamide.